Resurfacing capitate pyrocarbon implant as salvage procedure in several serious outcomes of carpal injuries. Clinical experience and follow-up - Marcuzzi, Augusto; Fulchignoni, Camillo; Teodori, Julien; Rocchi, Lorenzo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Resurfacing Capitate Pyrocarbon Implant has been introduced in the surgical practice as an alternative method to restore wrist motion, strength and functions in patients suffering from wrist osteoarthritis. It has already been well described in the literature as a treatment for advanced stages of degenerative wrist diseases which follow scaphoid’s and lunate’s injuries such as scapho-lunate advanced collapse, scaphoid non-union advanced collapse, and advanced stages of Kienböck disease. Authors extended the use of RCPI to other selected cases of complicated wrist injuries, spreading out from the classic indications for which this device was designed.Methods: We discuss 8 cases with serious outcomes of carpal injuries treated with Resurfacing Capitate Pyrocarbon Implant as salvage procedure between 2005 and 2013 by the first author of this paperResults: Among the eight particular selected cases, at a mean 4.3 years follow-up (range 2-11) only one was considered a failure and underwent a total wrist arthrodesis, resolving pain after all. The seven other cases reported good results. Range of Motion, Visual Analogue Scale for pain, subjective satisfaction and radiographical outcomes are reported.Conclusions: As a result of this heterogeneous clinical experience, validated by long-term follow-ups in most cases, we think that the use of a Resurfacing Capitate Pyrocarbon Implant can be suggested as an option in the outcomes of various carpal injuries.